Quebrando o silêncio: reflexos da construção da masculinidade na saúde mental dos homens - Izolan, Luana da Costa (2024)
The issue of how patriarchal society is structured and its reverberations in men's lives and their mental health remains insufficiently researched. It is known that the patriarchal system perpetuates the subordination of women and the superiority of men, impacting women's lives negatively in tangible ways, yet little is known about its impacts on men. Recent data on violence reveals that men constitute the majority of perpetrators of violent acts while also being the predominant victim group. Moreover, the male population also has the highest numbers in suicide rates, posing a serious public health issue. Therefore, this study aimed to understand how the construction of masculinity can affect men's mental health. Qualitative research was conducted through semi-structured interviews, and data were subsequently analyzed using dialectical hermeneutics methods. The study sample consisted of men aged 19 to 65 years old, with a mean age of 28.6 years (SD = 10.24), enrolled in undergraduate and postgraduate courses at a university in the interior of Rio Grande do Sul state. It has been concluded that the construction of masculinities primarily occurs through gendered socialization, which influences how men perform their masculinities differently depending on the social contexts they find themselves in. Society also plays a crucial role in dictating the nature of these performances. Furthermore, the results indicate that the current construction of masculinities has impacts on men's mental health, influencing how they express and cope with emotions and vulnerabilities, potentially leading to psychological distress.